A methodology for the SPICE-Compatible modelling of metal-semiconductor-metal photodetectors for nanophotonic interconnects application. (September 2021) - Qodratnama, Arash; Khunjush, Farshad; Raji, Mohsen
Abstract: On-chip global nanophotonic interconnects are promising alternatives to traditional metallic interconnects in giga-scale integrated circuits. At the very first step, the design and optimization of nanophotonic interconnects require the modelling and characterization of optoelectronic devices with irregular 3D geometries. In this paper, a methodology for the SPICE-compatible modelling of such devices is proposed which does not rely on post-manufacturing data. This methodology couples the optics and electronics domains of such devices in order to improve the model accuracy. The proposed methodology has been applied to the modelling of a waveguide-coupled integrated Metal-Semiconductor-Metal PhotoDetector (MSM PD) with quadratic nanotapers. We have performed optics domain simulation in 3D field-solver MEEP and device simulations using Silvaco Atlas device-TCAD tool. The simulation results agree well with measurement data reported in literature. Agreement with less than 12% error at all bias voltages is observed. Highlights: This article presents a methodology that characterizes an optoelectronic device without relying on measurement data. The presented methodology improves the modelling accuracy of metal-semiconductor-metal photodetectors. The methodology does not rely on post-manufacturing data to make design space exploration possible prior to manufacturing. The presented methodology couples the optics and electronics domains of functionality of the device.